Men, money & policy : essays in honor of Karl R. Bopp - Eastburn, David P.; Federal Reserve Bank of Philadelphia (Philadelphia : Federal Reserve Bank of Philadelphia, 1970)
Talks about men and the value of monetary policy in the Federal Reserve bank of Philadelphia.
Includes bibliographical references.
occ 15/01/2019
Loans
Keywords: Karl R. Bopp; Banks and Banking--Central.